Lifelong nutrition and bone health among the elderly. Validity of a food frequency questionnaire on intake at different periods of life, and the association between lifelong consumption of milk and cod liver oil and hip bone mineral density in old age - Tinna Eysteinsdóttir 1983- (2012)
Background: Few studies exist on the validity of food frequency questionnaires (FFQs) administered to elderly people. An FFQ on dietary intake during three different periods of life, adolescence (14-19y), midlife (40-50y) and current old age, was developed for the Age/Gene Environment Susceptibility (AGES) Reykjavik Study. Assessing the validity of the AGES-FFQ is important for its use in studies on diet-related disease risk and health outcomes, as incorrect information may lead to false associations between dietary factors and diseases. Milk is an important source of calcium and cod liver oil is a traditional source of vitamin D in Iceland. Consumption of both milk and cod liver oil is recommended for people of all ages in Iceland, not the least for the sake of bone health. However, whether and to what extent, lifelong consumption is associated with bone mineral density (BMD) in old age, the time of greatest risk of osteoporotic fractures, is unclear. The aim of the present thesis was to assess the validity of questions of the AGES-FFQ on midlife and current consumption. Furthermore, to assess the association between lifelong consumption of milk and cod liver oil and hip BMD in old age among participants of the AGES-Reykjavik Study. Also, the association between current intake of cod liver oil and serum 25(OH)D was assessed. Methods: Data was gathered from three different cohorts. For assessing the validity of questions on midlife diet, retrospective intake of 56-72-year old individuals was estimated using the AGES-FFQ and results compared with detailed dietary data, gathered from the same individuals 18-19 years previously, i.e. in midlife, as a part of a national dietary survey. Validity of questions on current intake was assessed by comparing answers from healthy elderly individuals (≥65y) to data obtained from 3-day weighed food records completed by the same individuals. Participants of the AGES-Reykjavik Study, age 66-96 years (N=4798, 44% male), answered the complete AGES-FFQ, including questions on milk ...